TOXIC EFFECTS OF HERBICIDE TRIBENURON-METHYL ON LIVER TISSUE OF ZEBRAFISH (DANIO RERIO) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Tribenuron-methyl (TBM) is a sulfonylurea group herbicide commonly used in weed control and integrated pest control in the world and in our country. As with all pesticides, its incorporation into the aquatic environment is dangerous for non-target organisms. Zebrafish (Danio rerio) is a freshwater fish that has been used frequently as a bioindicator species in the field of environmental toxicology in recent years. In this study, zebrafish were fed with pellet feed in tanks filled with chlorine-free water for 10 fish in each aquarium for two weeks. Experimental groups were exposed to 25, 50 and 100 ppm doses of TBM for 96 hours. The experiments were performed in triplicate. At the end of the period the liver organs of the fish were dissected and homogenized immediately. Then, reduced glutathione (GSH), malondialdehyde (MDA), total protein (TP) levels and acetylcholinesterase (AChE) and catalase (CAT) enzyme activities were determined by spectrophotometric methods. According to the findings, TP level and CAT enzyme activity increased in all doses compared to the control group. MDA levels decreased at all doses. AChE enzyme activity decreased at 25 and 50 ppm doses and increased at 100 ppm dose group. GSH levels increased in the 25 and 100 ppm group, but decreased in the 50 ppm group. In conclusion, TBM showed a detrimental effect on liver tissue enzyme activities and lipid peroxidation levels of zebrafish.
Keywords: Tribenuron-methyl; Oxidative stress; Zebrafish; Liver; OXIDATIVE STRESS; PESTICIDES; EXPOSURE